Prasugrel single antiplatelet therapy versus Aspirin and Clopidogrel dual antiplatelet therapy for flow diverter treatment for cerebral aneurysms: a retrospective multicenter study - Hohenstatt, Sophia; Saatci, Işıl; Jesser, Jessica; Çekirge, H. Saruhan; Koçer, Naci; Islak, Civan; Lücking, Hannes; DuPlessis, Johannes; Rautio, Riitta; Bendszus, Martin; Vollherbst, Dominik; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2024)
BACKGROUND AND PURPOSE: The optimal antiplatelet regimen after flow diverter treatment of cerebral aneurysms is still a matter of debate. A single antiplatelet therapy might be advantageous in determined clinical scenarios. This study evaluated the efficacy and safety of prasugrel single antiplatelet therapy versus aspirin and clopidogrel dual antiplatelet therapy. - MATERIALS AND METHODS: We performed a post hoc analysis of 4 retrospective multicenter studies including ruptured and unruptured aneurysms treated with flow diversion using either prasugrel single antiplatelet therapy or dual antiplatelet therapy. Primary end points were the occurrence of any kind of procedure- or device-related thromboembolic complications and complete aneurysm occlusion at the latest radiologic follow-up (mean, 18 months). Dichotomized comparisons of outcomes were performed between single antiplatelet therapy and dual antiplatelet therapy. Additionally, the influence of various patient- and aneurysm-related variables on the occurrence of thromboembolic complications was investigated using multivariable backward logistic regression. - RESULTS: A total of 222 patients with 251 aneurysms were included, 90 (40.5%) in the single antiplatelet therapy and 132 (59.5%) in the dual antiplatelet therapy group. The primary outcome-procedure- or device-related thromboembolic complications-occurred in 6 patients (6.6%) of the single antiplatelet therapy and in 12 patients (9.0%) of the dual antiplatelet therapy group (P = .62; OR, 0.712; 95% CI, 0.260-1.930). The primary treatment efficacy end point was reached in 82 patients (80.4%) of the single antiplatelet therapy and in 115 patients (78.2%) of the dual antiplatelet therapy group (P = .752; OR, 1.141; 95% CI, 0.599-2.101). Logistic regression showed that non-surface-modified flow diverters (P = .014) and fusiform aneurysm morphology (P = .004) significantly increased the probability of thromboembolic complications. - CONCLUSIONS: Prasugrel single antiplatelet therapy after flow diverter treatment may be as safe and effective as dual antiplatelet therapy and could, therefore, be a valid alternative in selected patients. Further prospective comparative studies are required to validate our findings.
Online veröffentlicht: 9. Mai 2024
Gesehen am 30.07.2024